2021
DOI: 10.1080/17441692.2020.1867879
|View full text |Cite
|
Sign up to set email alerts
|

Institutional overlap and access to medicines in MERCOSUR and UNASUR (2008–2018). Cooperation before the collapse?

Abstract: The proliferation of international and regional organizations in the last decades led to increasing overlap of memberships and mandates in social policy areas. Whereas the literature has explored the benefits and perils of institutional overlap though neglecting the social policy dimension of such processes, studies on regionalism have focused on single cases of regional organizations. This paper breaks new ground by examining the effects of the overlap in membership, health mandates and institutional mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Functional differentiation of regional cooperation will lead to a more complex, but possibly more robust regional governance structure, held together by overlapping membership. Latin America has a long tradition of overlapping regionalism (Bianculli et al, 2021; Weiffen et al, 2013) and cooperative regional governance (Nolte, 2014), which in the case of South America must now function without a “central organization” (Nolte, 2016) or “hub institution” (Cooper & Stubbs, 2017) such as Unasur. It carries the risk of a more segmented regional governance architecture.…”
Section: Exit Voice and Loyaltymentioning
confidence: 99%
“…Functional differentiation of regional cooperation will lead to a more complex, but possibly more robust regional governance structure, held together by overlapping membership. Latin America has a long tradition of overlapping regionalism (Bianculli et al, 2021; Weiffen et al, 2013) and cooperative regional governance (Nolte, 2014), which in the case of South America must now function without a “central organization” (Nolte, 2016) or “hub institution” (Cooper & Stubbs, 2017) such as Unasur. It carries the risk of a more segmented regional governance architecture.…”
Section: Exit Voice and Loyaltymentioning
confidence: 99%
“…Indeed, yellow fever was, at that time, the main disease affecting Latin America, and it pushed the region to dedicate much effort and attention to international health (Sacchetti and Rovere, 2011;Herrero and Belardo, 2022). Furthermore, in 1902, the Pan-American Health Organization (PAHO) was founded, becoming the world's oldest international public health organization and serving now as the WHO Regional Office for the Americas (Bianculli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The awareness that health and living conditions are mutually reinforcing has been growing over time, as has the emphasis on the role of social and health policies in addressing poverty and reducing inequalities, especially in Latin America, leading to the increasing recognition of health as a significant factor in international relations and regional policy agendas, particularly in the mentioned geography (Riggirozzi and Tussie, 2012;Herrero, 2017;Herrero et al, 2019). Latin America's history of international cooperation on health has evolved and expanded in the twenty-first century, in part enhanced by center-leftist governments in major parts of these countries that tend to promote new practices and arrangements in the sphere of social policy cooperation, despite this situation being reversed in the case of Brazil with the election of President Jair Bolsonaro in 2018 (Bianculli et al, 2021). In the Findings section, the impact of Jair Bolsonaro's mandates on health cooperation will be further discussed.…”
Section: Introductionmentioning
confidence: 99%
“…This brings us significantly closer given that one of the greatest advances on the regional agenda in South America in recent years has been in the area of medicines, through the price bank and joint purchases of high-cost medicines, which have been a great opportunity for strengthening national and regional capacities. 5 , 6 Regarding the Medicines Price Bank of UNASUR, the Group on Universal Access to Medicines of UNASUR, developed a database with the prices of drugs in all the countries of the region as a negotiating strategy. This information was a very useful tool during negotiations with the pharmaceutical companies.…”
mentioning
confidence: 99%
“…This information was a very useful tool during negotiations with the pharmaceutical companies. About, the joint negotiation of prices for high-cost medicines, this initiative contributed to save millions of dollars in joint purchases of medicines for hepatitis C. 5 , 6 Studies have shown that the articulation of countries through regional integration mechanisms such as UNASUR and the Southern Common Market, and with the participation of other regional instances, such as Pan-American Health Organization, led to economic savings in terms of drug purchases, with strategies of complementarity between the mechanisms, contrary to the overlapping of initiatives, such as the Joint Purchases of Medicines. Unfortunately, some of these processes were cut short due to the dissolution of UNASUR.…”
mentioning
confidence: 99%